2019
DOI: 10.23919/cjee.2019.000021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salty fog on flashover characteristics of OCS composite insulators

Abstract: To study the flashover characteristics of the fog water in saline-alkali areas for high-speed railway OSC insulators, the spatial distributions of both the potential and electric field of soiled insulators in the presence of salty fog are analyzed using COMSOL Multiphysics, a multi-physics coupling software. Furthermore, to analyze the effect of the contamination of insulators due to salty fog water , a saline solution is used for staining an insulator sample by using the solid coating method. In an artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The relevant data are used for setting the index threshold later. According to the specification [23][24][25][26][27] , together with the threshold determination method and onsite assessment experience [28][29][30] , the threshold values of the traction system's health status assessment [31][32][33] indexes are determined, as shown in Tab. 3.…”
Section: Index Parameters Of Traction Systemmentioning
confidence: 99%
“…The relevant data are used for setting the index threshold later. According to the specification [23][24][25][26][27] , together with the threshold determination method and onsite assessment experience [28][29][30] , the threshold values of the traction system's health status assessment [31][32][33] indexes are determined, as shown in Tab. 3.…”
Section: Index Parameters Of Traction Systemmentioning
confidence: 99%
“…Contamination (pollution, salinity, biological agents) can make the surface of the insulator more conductive, increasing the possibility of partial discharges (PDs), dry band arcing, and consequently decreasing the efficiency of the system [4]. Contamination is a problem in places close to industries, agriculture, mining, coastal regions, or unpaved streets that may accumulate on the surface of the insulators [5]. Therefore, in some critical locations, cleaning or washing the insulators is required to mitigate insulation failure in the power system [6].…”
Section: Introductionmentioning
confidence: 99%
“…It can accurately reflect the operating status of the insulator under multiple factors, and the cost is low. Wang et al [13] obtained the potential and electric field changes for insulator processed from corona discharge to flashover through simulation analysis of insulators in the operating state, which reflects the influence of various factors on the operating state of insulators. Lv et al [14] found that water droplets have a greater impact on the distortion rate of the electric field through simulation studies on the position, spacing, and parameters of the water droplets attached to the surface of the insulator.…”
Section: Introductionmentioning
confidence: 99%